Enhanced Accumulation of Bone Seekers at Superior Lateral Orbital Margin: Potential Origin - Swietaszczyk, Cyprian; Pilecki, Stanisław (World Journal of Nuclear Medicine, 2014)
Enhanced accumulation of the radiotracer at superior lateral orbital margin is a common finding in bone scintigraphy. Its possible sources are discussed and illustrated with examples from own archive of the authors as well as from the literature. These sources include: Physiologically enhanced bone metabolism at frontozygomatic suture (normal variant), a metastasis at this suture (illustrated with an example of solitary metastasis from prostate cancer), lesions to the zygomatic bone or the greater wing of the sphenoid bone, deepened fossa for lacrimal gland and the gland itself.
Keywords: Bone metastasis; bone scintigraphy; frontozygomatic suture; single-photon emission computed tomography/computed tomography; superior lateral orbital margin